Tunable near white light photoluminescence of lanthanide ion (Dy3+, Eu3+ and Tb3+) doped DNA lattices1. Issue 69 (29th July 2015) - Dugasani, Sreekantha Reddy; Park, Byeongho; Gnapareddy, Bramaramba; Pamanji, Sreedhara Reddy; Yoo, Sanghyun; Lee, Keun Woo; Lee, Seok; Jun, Seong Chan; Kim, Jae Hun; Kim, Chulki; Park, Sung Ha
<x xml:space="preserve">Abstract</x> We constructed lanthanide ion doped double-crossover DNA lattices grown on a silica substrate and studied their photoluminescence characteristics.